Moxifloxacin Induced Acute Delirium with Visual Hallucinations - Ergenekon Karagoz; Asim Ulcay; Asil Budakli; Recep Tutuncu (Medicine Science, 2015)
A few reports accuse and implicate moxifloxacin as a contributor to delirium state.Here, we report the A 60-year-old female patient, who developed acute delirium with visual hallucinations following treatment with moxifloxacin for atypical pneumonia. [Med-Science 2015; 4(3.000): 2694-9]